Surgical treatment of juvenile nasopharyngeal angiofibroma - Oré, Juan F. (2007)
Objectives: To describe the surgical handling of juvenile nasopharyngeal angiofibroma, both approach and anesthesia, to demonstrate compromise and staging and to determine complications and recurrence of juvenile angiofibroma using Le Fort I approach. Design: Retrospective descriptive study. Setting: Head and Neck Surgery Department, Hospital Dos de Mayo. Participants: Patients with pathology confirmed juvenile nasopharyngeal angiofibroma. Interventions: We reviewed all the cases with surgery for juvenile nasopharyngeal angiofibroma confirmed by pathology between January 1993 and December 2006. Main outcome measures: Surgical results, blood loss, complications. Results: We had 29 cases in the study period, all men, with average age 19,2 years, age rank 13 to 27 years. Most cases were from Lima (34%) and Cajamarca (17%). We report 90% of cases catalogued as Chandler III, 7% as Chandler IV and 3% as Chandler II. All received surgical treatment with submental intubation; in 28 patients Le Fort I approach was performed with titanium plates and screws osteosynthesis. Preoperative embolization was done when a transpalatine approach was decided. Preoperative hemoglobin was 13,6 g% average and postoperative 10,5 g%. We found an average blood loss of 1 019 mL, rank between 300 and 4 500 mL. Transfusion average was 2,3 red blood-cell packs by patient; three patients did not require transfusion. We did not have any postoperative complication. Conclusions: Surgery is the first treatment choice for any staging of juvenile nasopharyngeal angiofibroma. Due to the large surgical field with Le Fort I approach and few recurrences, we postulate this approach for all Chandler stages, especially Chandler III and IV. The accomplishment of Le Fort I approach and the submental intubation includes diverse concepts and techniques that define their complexity, like middle third facial osteotomies, osteosynthesis techniques, occlusal plane concept and its restoration.